NIBAN1, Exploring its Roles in Cell Survival Under Stress Context - Diana, Paula; Carvalheira, Gianna Maria Griz (Frontiers in Cell and Developmental Biology, 2022)
Cell survival must quickly activate specific mechanisms that enable to detect changes in the cellular microenvironment. The impact of these cell alteration has direct consequences on cellular homeostasis. Cellular stress, as well as its regulation and implication, has been studied in different pathologies. In this sense, the alteration in NIBAN1 expression seems to act in response to different cellular disturbances. Over the years, the knowledge of NIBAN1 functions has improved, demonstrating its important cell roles, favoring the cell survival under stress context. In response to the disturbances, NIBAN1 seems to be involved in the decision-making process between cell survival and death. The increase in NIBAN1 expression has been related to cellular mechanisms that seek to minimize the damage caused to cellular homeostasis. In this review, the main biological insights attributed to the NIBAN1 gene in different cellular contexts and its role as a mediator of cellular stress are discussed.